Military Career Adaptability Questionnaire in China: Development and Validation - Zhang, Wenmo; Xu, Yuanyuan; Peng, Li; Bian, Chen; Yu, Yongju; Li, Ying; Li, Min (Frontiers in Psychology, 2020)
Objective: To develop the Military Career Adaptability Questionnaire (MCAQ) in China and to test its reliability and validity. Methods: In study 1, an open-ended questionnaire survey was conducted among 200 military personnel. Based on the empirical construction by military personnel of various branches, the dimensions of the MCAQ were constructed and a preliminary questionnaire was prepared. In study 2, the questionnaire survey was conducted in 1578 participants enrolled through stratified cluster sampling. They were randomly divided into two groups (n=789). Sample 1 was used for item analysis and exploratory factor analysis, and sample 2 was used for confirmatory factor analysis and internal consistency testing. In sample 1, the participants were selected to test the test-retest reliability of the questionnaire at a 4-week interval. In sample 2, participants were selected to test criterion validity using the Psychological Capital Questionnaire and the Job Satisfaction Questionnaire. Results: According to study 1, we obtained an initial 23-item MCAQ containings five dimensions (organization and fusion ability, communication ability, learning development ability, emotion regulation ability and career transformation ability). After the exploratory factor analysis in study 2, 21 items contributing, 72.17% of the total variance remained. Via the subsequent confirmatory factor analysis, the model was confirmed to have good fit indices (X2/df = 3. 11, GFI = 0. 90, NFI = 0. 91, IFI = 0. 94, TLI = 0. 93, CFI＝0.94, RMSEA =0.07) . These five factors were significantly correlated with the total score of the MCAQ (r=0.73——0.79, p< 0.01). The Cronbach’s α coefficient of the questionnaire was 0.92; the Cronbach’s α coefficients of the five factors were 0.89, 0.83, 0.88, 0.84, and 0.79, respectively; the test-retest reliability of the questionnaire was 0.93. Conclusions: The Military Career Adaptability Questionnaire developed in this study has a clear five-factor structure and good reliability and validity. It can be used to assess the career adaptability of military personnel to provide a theoretical basis for military vocational psychological education.